Long-term fertilization altered microbial community structure in an aeolian sandy soil in northeast China - Zhang, Shiyu; Li, Xue; Chen, Kun; Shi, Junmei; Wang, Yan; Luo, Peiyu; Yang, Jinfeng; Wang, Yue; Han, Xiaori (Frontiers in Microbiology, 2022)
Soil microorganisms play crucial roles in nutrient cycling and determining soil quality and fertility; thus, they are important for agricultural production. However, the impacts of long-term fertilization on soil microbial community remain ambiguous due to inconsistent results from different studies. The objective of this study was to characterize changes in bacterial and fungal diversity and community structures after 12 years of different fertilization in aeolian sandy soil by analyzing 16S rRNA and ITS rRNA gene sequences and the soil properties to discover the driving factors. Eight different fertilizer treatments have been set up since 2009: no fertilizer (CK), chemical N fertilizer (N), chemical N and P fertilizer (NP), chemical N, P and K fertilizer (NPK), pig manure only (M), pig manure plus chemical N fertilizer (MN), pig manure plus chemical N and P fertilizer (MNP), pig manure plus chemical N, P and K fertilizer (MNPK). The results indicated that the long-term (12 years) application of chemical fertilizer reduced soil pH, whereas the addition of pig manure alleviated a decrease in soil pH value. Chemical fertilizer plus pig manure significantly improved soil fertility. Long-term MNPK fertilization resulted in changes in bacterial diversity due to effects on specific bacterial species; by contrast, all fertilization treatments resulted in changes in fungal diversity due to changes in soil properties. Principal component analysis indicated that fertilization had a significant effect on soil microbial community structure, and the effect of chemical fertilizer combined with pig manure was greater than that of chemical fertilizer alone. Soil available phosphorus, organic carbon, total nitrogen, total phosphorus, pH, nitrate nitrogen, and available potassium were the most important factors that influenced bacterial taxa, whereas soil pH, available phosphorus, total phosphorus, organic carbon, total nitrogen, and available potassium were the most important factors influencing fungal taxa after 12 years of fertilization in aeolian sandy soil.